Роль основного фактора росту фібробластів в регуляції обміну сполучної тканини у хворих на пролапс мітрального клапану з цукровим діабетом I типу - Ніколенко, Олена Євгенівна; Nikolenko, Olena Ye. (Харків: ХНУ імені В.Н. Каразіна, 2021)
Olena Ye. Nikolenko. The role of the fibroblast growth factor-2 in the regulation of connective tissue metabolism in patients with mitral valve prolapse and type 1 diabetes mellitus. – Qualification scientific work on the rights of the manuscript. The dissertation on competition of a scientific degree of the candidate of medical sciences on a specialty 14.01.02 – internal diseases (Medical sciences) – V. N. Karazin Kharkiv National University, the Ministry of Education and Science of Ukraine, Kharkiv, 2021. The primary goal of the research is to increase the efficiency of the early diagnosis and the prognosis about the course of mitral valve prolapse (MVP) in combination with type I diabetes mellitus (DM I), by specifying the interdependences in the pathogenesis of connective tissue (CT) dysplasia of the MV and left ventricular (LV) myocardium, based on the study of the fibroblast growth factor-2 (FGF-2), CT metabolism and echocardiographic (EchoCG) data among young people.
The role of the fibroblast growth factor-2 in the regulation of connective tissue metabolism in patients with mitral valve prolapse and type 1 diabetes mellitus
Робота присвячена підвищенню ефективності ранньої діагностики та прогнозування перебігу пролапсу мітрального клапана з цукровим діабетом I типу шляхом дослідження регуляції фибриллогенезу, показників метаболізму сполучної тканини та ехокардіографічних даних. Було встановлено, що при поєднанні пролапсу мітрального клапану та цукрового діабету І типу відзначається зростання пептиднозв’язаного оксипролину, фактора росту фібробластів FGF-2, II фракції глікозоаміногліканів. Показано, що структурно-функціональні параметри мітрального клапану і лівого шлуночка корелювали з показниками регуляції та обміну сполучної тканини. Встановлено прогностичне значення щодо ремоделювання міокарду та дегенерації мітрального клапана FGF-2, індексу відносної товщини стінки лівого шлуночка, тривалості перебігу діабету > 10 років.
Keywords: пролапс мітрального клапану; цукровий діабет І типу; основний фактор росту фібробластів (FGF-2); обмін оксипролину; фракції глікозоаміногліканів; ехокардіографічні показники; mitral valve prolapse; type 1 diabetes mellitus; FGF-2; oxyproline metabolism; fractions of glycosaminoglycans; echocardiographic signs